2015
DOI: 10.1002/jbmr.2555
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increased Calcium and Calcitriol Requirements After Discontinuation of Human Synthetic Parathyroid Hormone 1-34 (hPTH 1-34) Replacement Therapy in Hypoparathyroidism

Abstract: Synthetic human PTH 1-34 (hPTH 1-34) replacement therapy in hypoparathyroidism maintains eucalcemia and converts quiescent bone to high-turnover bone. However, the skeletal and metabolic effects of drug discontinuation have not been reported. Nine subjects with hypoparathyroidism received subcutaneous injections of hPTH 1-34 two to three times daily for 19.8 to 61.3 months and then transitioned back to calcium and calcitriol. Biochemistries and bone mineral density (BMD) by dual-energy X-ray absorptiometry (DX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
(51 reference statements)
1
24
0
Order By: Relevance
“…Subjects were evaluated at the Clinical Center of the NIH (Bethesda, MD, USA) every 6 months. After the last visit on hPTH 1‐34, the drug was weaned as previously described, with all subjects resuming conventional therapy with calcium and calcitriol. Subjects then returned to the NIH for a follow‐up visit (FU) 6 to 12 months after the last visit on hPTH 1‐34.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects were evaluated at the Clinical Center of the NIH (Bethesda, MD, USA) every 6 months. After the last visit on hPTH 1‐34, the drug was weaned as previously described, with all subjects resuming conventional therapy with calcium and calcitriol. Subjects then returned to the NIH for a follow‐up visit (FU) 6 to 12 months after the last visit on hPTH 1‐34.…”
Section: Methodsmentioning
confidence: 99%
“…The anabolic effects of hPTH(1-34) are followed by excessive bone resorption. Increasing the dosage of PTH treatment is complicated, involving serious side effects of hypercalcemia and cortical porosity (26,27). Therefore, new development of PTH or PTHrp analogues with purer anabolic activity, such Abaloparatide, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Gafni et al . also showed in a small cohort followed for 20–60 months, a small effect of PTH (1–34) to reduce BMD at the distal 1/3 radius and the lumbar spine .…”
Section: Pathophysiological Effects Of Pth – Clinical Manifestations mentioning
confidence: 77%
“…BMD Z‐scores were +2.2 at the lumbar spine, +1.3 at the femoral neck, +1.1 at the total hip and +0.64 at the distal 1/3 radius . Treatment with PTH either by teriparatide [PTH (1–34)] or PTH (1–84) generally shows an increase or unchanged BMD at the lumbar spine and hip, but a small decrease at the distal 1/3 radius. Further work by Cusano et al ., in a 4‐year longitudinal study, showed that the small decline in the distal 1/3 radius site was, at the end of the study period, not different from baseline .…”
Section: Pathophysiological Effects Of Pth – Clinical Manifestations mentioning
confidence: 99%